De novo transcriptome sequencing to identify the sex-determination genes in Hyriopsis schlegelii. Issue 8 (3rd August 2015) - Shi, Jianwu; Hong, Yijiang; Sheng, Junqing; Peng, Kou; Wang, Junhua
Abstract: This study presents the first analysis of expressed transcripts in the spermary and ovary of Hyriopsis schlegelii ( H. schlegelii ). A total of 132, 055 unigenes were obtained and 31, 781 of these genes were annotated. In addition, 19, 511 upregulated and 25, 911 downregulated unigenes were identified in the spermary. Ten sex-determination genes were selected and further analyzed by real-time PCR. In addition, mammalian genes reported to govern sex-determination pathways, including Sry, Dmrt1, Dmrt2, Sox9, GATA4, and WT1 in males and Wnt4, Rspo1, Foxl2, and β - catenin in females, were also identified in H. schlegelii . These results suggest that H. schlegelii and mammals use similar gene regulatory mechanisms to control sex determination. Moreover, genes associated with dosage compensation mechanisms, such as Msl1, Msl2, and Msl3, and hermaphrodite phenotypes, such as Tra - 1, Tra - 2α, Tra - 2β, Fem1A, Fem1B, and Fem1C, were also identified in H. schlegelii . The identification of these genes indicates that diverse regulatory mechanisms regulate sexual polymorphism in H. schlegelii . Graphical abstract: : 19, 511 upregulated and 25, 911 downregulated genes were detected in the spermary compared to the ovary, including many sex determination and differentiation genes.